طريقة كيموتألقية - حقن جرياني مستمر لتقدير االتينولول معتمدا على النظام الكيموتألقي للومينال - هيدروكسيد الصوديوم-بيروكسيد الهيدروجين - الهاشمي, عصام محمد علي شاكر; العوادي, نغم شاكر تركي (Al-Nahrain Journal of Science, 2013)
Atenolol was determined in six pharmaceutical product of different manufacturer via the chemiluminescence system for the oxidation of Luminol-atenolol derivative in alkaline solution using continuous flow injection analysis using a sample of 85µl of Atenolol that was injected on a distilled water carrier stream which gave white blue which has max emission of 450 nm. A scatter diagram for the variation of Atenolol concentration versus chemiluminescence response was obtained; linear calibration graph for 0.1-20 mM.L-1 with C.O.D of 97.39% while L.O.Q of 257 µg/85µl with a L.O.D at S/N=3 was 113 ng/85µL via the gradual dilution for the lowest concentration in the calibration graph. The R.S.D% for 10mM.L-1 was 0.43% (n=10). The developed method for analysis was applied satisfactorily for the determination of Atenolol in pharmaceutical drugs using direct calibration graph and the standard addition method. It was found that the later was more representative in expressing the results via the recovery percentage as at was between 95.32-100.98% with no systemic error. A comparison was made between the classical spectrophotometric method and the new method for all six samples. Using standard addition method and paired t-test. It was found that there were no significant difference at 95% confidence internal i:e the newly developed method for Lu-OH--H2O2-Atenolol can be accepted as an alternative analysis method.